Reflections on Five Decades of the Fontan Kreutzer Procedure - Kreutzer, Christian; KREUTZER, JACQUELINE; Kreutzer, Guillermo O. (Frontiers in Pediatrics, 2013)
The first successful total right heart bypass via atriopulmonary anastomosis, (APA) were reported in 1971 for patients with tricuspid atresia. At the Children´s Hospital of Buenos Aires, the cohort of such procedures started in July, when the first fenestrated right heart by pass was performed, with the interposition of a homograft between the right atrial appendage and the main pulmonary artery. In the second patient, instead of placing a homograft, the APA was achieved with the patient´s own pulmonary root harvested from the outflow tract of the right ventricle. These techniques were soon replaced in 1978 with the development of the direct valveless posterior atriopulmonary anastomosis. Since the very beginning the principle was that the right atrium only functions as a pathway rather than a pump (reason why no inferior vena cava valves were ever used), and the diastolic properties of the systemic ventricle regulate the only real “pump” of this system. The late hemodynamic problems inherent of the APA diminished with modern surgical techniques like the lateral tunnel (LT) or the extracardiac conduit (EC). In spite of the improvement in prognosis and quality of life that the modern techniques have brought for univentricular hearts, with the passing of time, deterioration of this system is frequently seen, due to chronic low cardiac output and elevated central venous pressure. Progressive increase in pulmonary vascular resistances and ventricular dysfunction result in a decline in quality of life and survival. However, the timing of this occurrence is variable, and many survivors enjoy today a satisfactory clinical status. The challenge is to develop a better solution for univentricular hearts, but in the mean time the Fontan Kreutzer palliation represents the best and only surgical option. It is undoubtedly one of the triumphs of cardiac surgery in congenital heart disease.